Interaksi Nilai Pasar, Pertumbuhan, dan Struktur Modal pada Kebijakan Dividend Payout - Intan Syahfitri, Diah (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study explores the dynamic and multifaceted interactions between market value, growth opportunities, and capital structure in shaping corporate dividend payout policies through a systematic literature review (SLR) and comprehensive bibliometric analysis. By analyzing a corpus of data consisting of 50 Sinta-accredited journal articles and international ISSN journals published in the last decade, this study maps research trends, central themes, and conceptual evolution in the domain of global corporate finance. Using VOSviewer software for intellectual network visualization, this study identifies key thematic clusters covering agency theory, market signals, funding hierarchy (pecking order), and corporate life cycle. Key findings show that interactions between variables are not linear, but rather form a complex equilibrium: high growth opportunities tend to suppress dividend payout ratios in favor of profit retention, but market value pressures often force management to maintain dividends as a mechanism for signaling stability. On the other hand, capital structure functions as a double-edged sword, where debt can be a substitute for dividend discipline or a strict liquidity constraint. This study also reveals a “dividend policy paradox” in emerging markets, where companies often make payout decisions that deviate from financial fundamentals in order to mitigate severe information asymmetry. This study makes an original contribution by synthesizing fragmented literature into an integrative framework, offering practical implications for financial managers in navigating strategic trade-offs, and providing policy recommendations for capital market regulators.